Using Artificial Intelligence Methodologies in Examining Parenting Behaviors and Services - Robila, Mihaela; Robila, Stefan A (Research in Social Sciences and Technology, 2026)
Artificial intelligence methodologies have been successfully applied to different areas of behavioral and social sciences, such as increasing effectiveness of diagnosis and prediction of different conditions, increasing understanding of human development and functioning, as well as increasing the effectiveness of data management in different social and human services, many of them focused on parenting. The goal of this article is to provide a systematic examination of artificial intelligence and machine learning methodologies that are currently employed to analyze parenting behaviors and to implement and deliver parenting programs and services. Enabled by transformative technological advances, social and human services on parenting are redesigned to better serve a diverse society through increased digitization and automation and workforce retraining based on new evidence-based approaches. The examination reveals that AI has already become a pervasive trait among vast areas of parenting research and programs. Beyond identifying themes around the use of AI in the context of parenting, ethical issues, such as ensuring equity and fairness of access to services through technology have been addressed.